Asuhan Keperawatan Pada Ny. D Dengan Stroke Iskemik - Utami, Meilani (Jurnal Ilmiah Cerebral Medika, 2025)
Ischemic stroke is a type of stroke caused by blockage of blood vessels in the brain, resulting in reduced oxygen supply to the brain and subsequent cell or tissue death. According to the World Health Organization (WHO) in 2021, the global incidence of stroke reached 15 million cases, resulting in 5 million deaths. According to medical records from RS TK III RS Reksodiwiryo Padang, the highest number of ischemic stroke patients occurred in November, with 33 cases and 3 deaths. The purpose of this study is to provide emergency nursing care to Ny. D with ischemic stroke. The research method used is a case study with a descriptive approach, including the nursing process of assessment, diagnosis, intervention, implementation, and evaluation. This study was conducted from April 23 to 25, 2022. The participant in this study was Ny. D with ischemic stroke in the Rasuna Said room at RS TK III dr. Reksodiwiryo Padang. The assessment results showed that Ny. D experienced headaches, weakness in the left limb, and high blood pressure. The nursing problems that emerged were impaired physical mobility, risk of falls, and readiness for family coping enhancement. The interventions to be implemented include mobilization support, Management of increased intracranial pressure, and family involvement. After implementation, the nursing problems were partially resolved, as Ny. D was still unable to transfer from a wheelchair to bed independently. It is recommended that future researchers emphasize ROM therapy training for patients.